Psychological and Pedagogical Features of Students’ Adaptation to Studying at Higher Education Institutions - Iliichuk, Liubomyra; Vorobets, Oleksii (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article describes the peculiarities of the process of students' adaptation to studying at a higher education institution, emphasizes the relevance of this problem in the context of the issue of training highly qualified specialists capable of effective work in the specialty at the level of world standards, ready for continuous professional improvement and personal development. The paper emphasized that the period of adaptation is a particularly important stage of studying at a higher education institution. It is particularly relevant when higher education students adapt to the content and nature of the educational process, in the period of adoption of norms and requirements of the new social environment, inclusion in the system of interpersonal relations, formation of a system of personal orientations, values, necessary for professional activity. The relationship between students' academic success and their level of adaptation to studying at a higher education institution has been identified. The results of an experimental study are presented, where the main factors of adaptation of higher education students, affecting their activity and academic success, are identified. Among these factors, the authors singled out magnitude of educational and extracurricular workload, working capacity during the school day and week, health condition, manifestation of various signs of fatigue, self-efficacy, motivation to learning, relationships with classmates and teachers, social frustration. The researchers stressed that the first-year students' adaptation period is different, depending on their individual and psychological characteristics, the level of readiness to study at a higher education institution, the correct choice of the future profession. On the basis of the results of the experimental study, the ways and directions of successful students' adaptation are determined, which foresees, first of all, the reduction of the impact of maladaptation factors on higher education students, increase in their resistance to these factors and strengthening of those factors that are favorable to them.